2021
DOI: 10.1093/ageing/afab126
|View full text |Cite
|
Sign up to set email alerts
|

External validation of the Hospital Frailty Risk Score in France

Abstract: Background The Hospital Frailty Risk Score (HFRS) has made it possible internationally to identify subgroups of patients with characteristics of frailty from routinely collected hospital data. Objective To externally validate the HFRS in France. Design A retrospective analysis of the French medical information database. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 41 publications
4
48
0
Order By: Relevance
“…This may partly be explained by the potential misclassification of readmission, since we did not have data on patients who were admitted to other clinics than the nine geriatric clinics. Besides, a relatively low AUC or c-statistic for frailty in predicting readmission (around 0.5–0.6) is also frequently reported in the literature (19,22,23,33,42,43). Hospital readmission is often described as a complex outcome not merely related to the health status of patients, but also social factors such as access to care, social support, and drug abuse (44,45), which are factors not captured in the frailty measures.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This may partly be explained by the potential misclassification of readmission, since we did not have data on patients who were admitted to other clinics than the nine geriatric clinics. Besides, a relatively low AUC or c-statistic for frailty in predicting readmission (around 0.5–0.6) is also frequently reported in the literature (19,22,23,33,42,43). Hospital readmission is often described as a complex outcome not merely related to the health status of patients, but also social factors such as access to care, social support, and drug abuse (44,45), which are factors not captured in the frailty measures.…”
Section: Discussionmentioning
confidence: 83%
“…While these tools are commonly used on data retrieved from primary care, recent studies have shown that such eFIs show good predictive performance for all-cause mortality also in hospital settings (1921). Another database-derived frailty measure, the Hospital Frailty Risk Score (HFRS), is calculated based on the International Classification of Diseases, Tenth Revision (ICD-10) codes (22), and has been validated for its ability to predict mortality and prolonged length of stay in hospitalized older patients (2325). However, its composition of ICD-10 diagnoses makes it more similar to a comorbidity measure, possibly missing out other frailty aspects such as functioning (22).…”
Section: Introductionmentioning
confidence: 99%
“…Prior HFRS studies focused on validating it in general hospitalizations, including non-ICU and ICU patients 17 19 , 36 39 . Recently, there has been interest in externally validating the HFRS in ICU administrative databases, as interest in big data frailty research increases 21 , 40 , 41 .…”
Section: Discussionmentioning
confidence: 99%
“…We only evaluated in-hospital all-cause mortality instead of 30-day mortality (inpatient or outpatient) because the NRD only records in-hospital deaths. We defined prolonged hospitalization as a hospital length of stay > 10 days and only evaluated 30-day emergency hospital readmissions, similar to Gilbert et al 16 , 17 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation